The Effects of cAMP-elevating Agents and Alpha Lipoic Acid on In Vitro Maturation of Mouse Germinal Vesicle Oocytes - A Rahnama; S Zavareh; MT Ghorbanian; I Karimi (JRI, 2013)
Background: In spite of extensive efforts to improve in vitro oocyte maturation, the obtained results are not very efficient. This study was conducted to assess impacts of cAMP elevating agents and alpha lipoic acid (ALA) on in vitro oocyte maturation and fertilization. Methods: Mouse germinal vesicle (GV) oocytes were categorized into cumulus denuded oocytes (DOs; n=896) and cumulus oocyte complexes (COCs; n=1077) groups. GV oocytes were matured in vitro with or without ALA; (I) without the meiotic inhibitors; (II) supplemented with cilostamide; (III) supplemented with forskolin and (IV) supplemented with Forskolin plus cilostamide. The obtained metaphase II (MII) oocytes were subjected to in vitro fertilization. Independent-samples t-testand ANOVA were used for data analysis. A p-value less than 0.05 was considered to be statistically significant. Results: The COCs maturation, fertilization and two cell embryo rates were higher than those of DOs in the control group, while no significant difference was observed between relevant COCs and DOs when they were cultured with cilostamide meiotic inhibitors in two step manner. Combined treatment of cilostamide and forskolin significantly elevated the developmental rates in both COCs and DOs as compared to other groups. The developmental rates of COCs and DOs in the presence of ALA were similar to their respective groups without ALA. Conclusion: cAMP elevating agents were more effective on DOs than COCs with regard to rates of maturation and fertilization. However, ALA did not affect the developmental rates of both COCs and DOs in in vitro maturation in one or two step manner.
Keywords: ALA, cAMP-elevating agents, Cumulus cell, In vitro maturation, Mouse, Oocyte